(untitled) (Journal of Enam Medical College, 2012)
Background: Abnormalities in lipid metabolism are associated with renal diseases. Association of serum lipid parameters with renal function is less studied in subjects with type 2 diabetes in Bangladeshi population. Objective: To assess the correlation of high density lipoprotein cholesterol with glomerular filtration rate (GFR) in type 2 diabetic subjects. Materials and Methods: One thousand three hundred thirty confirmed diabetic subjects advised for HbA1c, serum creatinine, serum total cholesterol, serum triglycerides, serum HDL cholesterol and LDL cholesterol were included in the study. Serum total cholesterol, HDL cholesterol, triglyceride, serum creatinine, HbA1c were measured by standard methods and serum LDL cholesterol was calculated by Friedewalds formula. GFR was calculated by MDRD4 variables prediction equation. Total subjects were grouped according to sex; both males and females were subdivided into three subgroups depending on GFR values. Results of lipid parameters were compared by one-way ANOVA among different groups and correlation of lipid parameters with GFR were expressed by Pearson r. Results: HDL cholesterol was significantly different among different GFR groups (p<0.05) and positively correlated with GFR (r = 0.1386, p<0.001) in males. Total cholesterol and LDL cholesterol showed feeble positive correlation with GFR (r = 0.0789, p<0.05 for total cholesterol and r = 0.0768, p<0.05 for LDL cholesterol), but are not significantly different among GFR groups (p>0.05) in males. Total cholesterol, HDL cholesterol, LDL cholesterol, non-HDL cholesterol and LDLC/HDL-C were significantly different among three different GFR groups (p<0.01) and only HDL cholesterol and LDL-C/HDL-C showed weak correlation with GFR (r = 0.0770, p<0.05 for HDL cholesterol and r = -0.0803, p<0.05 for LDL-C/HDL-C) in females. Conclusion: The study revealed that HDL cholesterol was significantly and positively correlated with glomerular filtration rate in both male and female diabetic subjects and assessment of lipid parameters might be a helpful tool to prevent or delay the progression of renal insufficiency. DOI: http://dx.doi.org/10.3329/jemc.v2i1.11916 J Enam Med Col 2012; 2(1): 15-19